Hubungan Asupan Makronutrien (Karbohidrat, Lemak, Protein) dan Kadar Hemoglobin dengan Prestasi Belajar Pada Remaja Putri di SMA N 1 Polokarto Kab. Sukoharjo - Arifah, Khoirina Nur, Dwi Sarbini, S.ST., M.Kes, Setia Asyanti, S.Psi., M.Si (2016)
Makronutrient intake (carbohydrate, lipid, protein) are major factor that provides energy for the optimum brain. Besides makronutrient intakes, oxygen that is taken by hemoglobin is another factor that influences the brain performance. The brain that works optimum can increase learning achievement. Research by the District Health Office of Sukoharjo in 2014 showed that the largest percentage of anemia found in SMA N 1 Polokarto is 68%. To determine the relationships which was between macronutrient intakes (carbohydrate, lipid, protein) and hemoglobin levels with learning achievement at SMA N 1 Polokarto, Sukoharjo. This observational research is used cross-sectional approach. Subjects in this research were 68 students that had been through chosen purposive random sampling. The data of macronutrient intake were obtained using 3x24 hour food recall, the hemoglobin levels were measured using Cyanmethemoglobin method, while data on learning achievement were obtained by looking at the average value of the Final Exam of the even semester 2015/2016 academic test. Statistical test used Person Product Moment test. The results showed that majority of students had a moderate carbohydrate intake (67.6%), low lipid intake (79.4%), low protein intake (48.5%), abnormal hemoglobin levels (54.4%) and learning achievement sufficient (63.2%). There was a relationship between carbohydrate intake and learning achievement (p=0.033). There was no relationship between lipid intake and academic achievement (p=0.884). There was no relationship between protein intake and academic achievement (p=0.646). There was a relationship between hemoglobin levels and academic achievement (p=0.000).